2016
DOI: 10.1099/jmm.0.000197
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of Bifidobacterium longum expressing α-melanocyte-stimulating hormone to combat ulcerative colitis

Abstract: a-Melanocyte-stimulating hormone (a-MSH) is a tridecapeptide derived from proopiomelanocortin that exhibits potent anti-inflammatory properties by regulating the production of inflammatory mediators. This peptide has been well established in several inflammatory models, including inflammatory bowel disease (IBD). However, its extremely short duration in vivo limits its clinical application. To address this limitation, Bifidobacterium was used here as a carrier to deliver a-MSH. We utilized a-MSH-engineered Bif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…In the first of these reports, preventive daily oral administration of α-MSH-secreting B. longum HB15 (HB15) markedly reduced histopathological damage, increased myeloperoxidase activity, corrected an inflammatory/anti-inflammatory cytokine imbalance, and induced production of the pro-inflammatory factor nitrogen monoxide, overcoming effects caused by DSS colitis in rats. Administration of WT-HB15 improved all the parameters with the exception of nitrogen monoxide production, but to a considerably lower degree than that seen with the recombinant strain (19). In the second report, α-MSH-secreting B. longum HB25 (HB25) was created.…”
Section: Bifidobacteriummentioning
confidence: 73%
See 1 more Smart Citation
“…In the first of these reports, preventive daily oral administration of α-MSH-secreting B. longum HB15 (HB15) markedly reduced histopathological damage, increased myeloperoxidase activity, corrected an inflammatory/anti-inflammatory cytokine imbalance, and induced production of the pro-inflammatory factor nitrogen monoxide, overcoming effects caused by DSS colitis in rats. Administration of WT-HB15 improved all the parameters with the exception of nitrogen monoxide production, but to a considerably lower degree than that seen with the recombinant strain (19). In the second report, α-MSH-secreting B. longum HB25 (HB25) was created.…”
Section: Bifidobacteriummentioning
confidence: 73%
“…In 2015, Zhang et al showed that the Treg/Th17 balance that had broken down as a result of DSS colitis was fully restored by gm-NCC2705 through the inhibition of two intracellular signaling pathways for Th17 induction (22). In 2016, the intestinal inflammation amelioration action of different strains of B. longum that produced human α-MSH was reported (19, 20). In the first of these reports, preventive daily oral administration of α-MSH-secreting B. longum HB15 (HB15) markedly reduced histopathological damage, increased myeloperoxidase activity, corrected an inflammatory/anti-inflammatory cytokine imbalance, and induced production of the pro-inflammatory factor nitrogen monoxide, overcoming effects caused by DSS colitis in rats.…”
Section: Bifidobacteriummentioning
confidence: 99%
“…Codon optimization for increased protein expression in B. longum , such as expression of alpha‐melanocyte‐stimulating hormone (Wei et al . ), antigenic fragments of viral proteins (Shkoporov et al . ), hepatitis C virus non‐structural protein (Takei et al .…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid pBV220‐rho was constructed from pBV220 (Wei et al, ), rho sequence, and rho‐asRNA were inserted into pBV220 and named pBV220‐rho(+) and pBV220‐rho(−), respectively. The plasmid was transformed into E .…”
Section: Methodsmentioning
confidence: 99%